Communicable Diseases Surveillance: CDI volume 30 issue 1 (2006) - No authors listed (Communicable Diseases Intelligence, 2006)
Communicable diseases surveillance outcomes from several reporting series as follows: Highlights for 4th quarter, 2005 (gastrointestinal illnesses, sexually transmissible infections, vaccine preventable diseases, vectorborne diseases, other bacterial infections; National Notifiable Diseases Surveillance System tables, 1 October to 31 December 2005; Laboratory Serology and Virology Reporting Scheme tables, 1 October to 31 December 2005; Australian Sentinel Practices Research Network, reporting period 1 October to 31 December 2005 (cumulation of year to date); Australian childhood immunisation coverage, 1 July to 30 September 2005 cohort, assessed as at 31 December 2005; Gonococcal surveillance, reporting period 1 July to 30 September 2005; HIV and AIDS surveillance, reporting period 1 July to 30 September 2005, assessed as at 31 December 2005; National Enteric Pathogens Surveillance System, reporting period 1 October to 31 December 2005.